Effect of Daily Temperature Fluctuation during the Cool Season on the Infectivity of Cryptosporidium parvum - Li, Xunde (American Society for Microbiology (ASM), 2010)
The present work calculated the rate of inactivation of Cryptosporidium parvum oocysts attributable to daily oscillations of low ambient temperatures. The relationship between air temperature and the internal temperature of bovine feces on commercial operations was measured, and three representative 24-h thermal regimens in the ∼15°C, ∼25°C, and ∼35°C ranges were chosen and emulated using a thermocycler. C. parvum oocysts suspended in deionized water were exposed to the temperature cycles, and their infectivity in mice was tested. Oral inoculation of 10(3) treated oocysts per neonatal BALB/c mouse (∼14 times the 50% infective dose) resulted in time- and temperature-dependent reductions in the proportion of infected mice. Oocysts were completely noninfectious after 14 24-h cycles with the 30°C regimen and after 70 24-h cycles with the 20°C regimen. In contrast, oocysts remained infectious after 90 24-h cycles with the 10°C regimens. The estimated numbers of days needed for a 1-log(10) reduction in C. parvum oocyst infectivity were 4.9, 28.7, and 71.5 days for the 30, 20, and 10°C thermal regimens, respectively. The loss of infectivity of oocysts induced by these thermal regimens was due in part to partial or complete in vitro excystation.